An exploration of ethnic entrepreneurial values and characteristics in MSEs - Elsye Tandelilin; Dwi Ratmawati; Tri Siwi Agustina (Universitas Negeri Surabaya, 2021)
Entrepreneurship is one aspect that can encourage economic growth in a country through the creation of goods and services, it can improve the welfare of society. However, the survival of micro and small enterprises (MSEs) is still lower. Even though the number of MSEs in Indonesia has increased, the failure elevates. Variables that can increase the success of MSEs include the values and characteristics of the entrepreneur. This paper explores the entrepreneurial values and characteristics of Chinese, Javanese, and Madurese ethics in MSEs. This study uses a case study approach by using in-depth interviews to explore detailed information. The data source is primary data with six informants from three different ethnicities (Chinese, Javanese, and Madurese). The results demonstrate that Indonesian Chinese entrepreneurs uphold values and dominant perseverance, hard work, guanxi, honesty, personal trust, and confucianism values. Meanwhile, Javanese entrepreneur implements family values, spirituality, innate, paternalism, creativity, deliberation, and harmony. Finally, Madurese entrepreneur emphasizes obedience/surrender to parents, fraternity, and natural behaviour.